Optimization of round shape floating LNG supply chain efficiency with simulation modeling - Sanusi, Sanusi (2013)
Supply chain management plays very pivotal role in business operation of LNG due to increase of gas demand and need of optimization of supply chain process to achieve high profitability and customer satisfaction. Optimum LNG supply chain is obtained through the integration among states in supply chain and high utilization of facilities in every single stage. Integration of those stages should be considered in early stages before actual operation is performed. An effort to integrate LNG supply chain to get optimum performance requires simulation modeling. Critical factors impact the performance metrics were identified by using statistical design of experiment principles, subsequently simulation modeling was used to evaluate various what if (experiments) for determining the interaction among the factors and significance of the factors in LNG supply chain. In the simulation, the critical factors such as storage capacity, offloading rate, transportation capacity and number of LNG carrier were identified. The results of this study indicate that transportation capacity and number of LNG carrier are the most significant factors in achieving optimal amount of LNG in receiving terminal and high performance of LNG carrier. Then, the obtained result was used to design LNG supply chain of Round Shape FLNG using Visual Basic (VB). From the simulation, it is concluded that the optimal balancing of LNG supply chain with 997 tonnage per hour for production capacity requires seven LNG carriers with capacity 93,900 tonnage, storage capacity 288,530 tonnage and offloading rate 7940 tonnage per hour. This combination resulted the amount of received LNG in receiving about 8,013 million tonnage per year and performance of LNG Carrier is about 99,85 %